Falling Behind: Has Rising Inequality Fueled the American Debt Boom? - Moritz Drechsel-Grau; Fabian Greimel (CESifo GmbH, 2024)
This paper studies whether the interplay of social comparisons in housing and rising income inequality contributed to the household debt boom in the US between 1980 and 2007. We develop a tractable macroeconomic model with general social comparisons in housing to show that changes in the distribution of income affect aggregate housing demand, aggregate debt and house prices if (and only if) social comparisons are asymmetric. In the empirically relevant case of upward-looking comparisons, rising inequality can rationalize a substantial share of the observed housing and debt boom.
Keywords: D14; D31; E21; E44; E70; R21; 330; mortgages; housing boom; social comparisons; consumption networks; external habits; keeping up with the Joneses